The Oxford handbook of philosophy of time - Callender, Craig (Oxford handbooks., 2011)
As the study of time has flourished in the physical and human sciences, the philosophy of time has come into its own as a lively and diverse area of academic research. Philosophers investigate not just the metaphysics of time, and our experience and representation of time, but the role of time in ethics and action, and philosophical issues in the sciences of time, especially with regard to quantum mechanics and relativity theory. This Handbook presents twenty-three specially written essays by leading figures in their fields: it is the first comprehensive collaborative study of the philosophy of time, and will set the agenda for future work.